Yield optimization of sweet corn (Zea mays L.) in response to soils, plant densities and application of plant growth regulators - Saiin, Sebrina Shahniza (2020)
Soils, plant densities and application of plant growth regulators are three of the major factors affecting sweet corn growth and yield. Although many worldwide studies were done to evaluate the effect of these factors on sweet corn, it is still necessary to do more study in this area because environmental factors will give significant effect to growth and yield of sweet corn since local farmers in selected locations adopted different plant densities yet they claimed their practices produced the same yield as manual. Meanwhile, the increase of land use for agriculture in Malaysia is focusing on industrial crops causing significant decrease in land use for food crops which eventually affected food security. The objective of this study is to assess yield optimization through different plant densities for different type of soils with application of plant growth regulators for sweet corn (Zea mays L.) cultivation. Both experiments were performed using split-split plot design with four replications using a variety of sweet corn seed Akik SC422. Analysis of Variance (ANOVA) with probability value of @ 0.05 using LSD was used to analyze the obtained data. Regression analyses were performed using Nonlinear Regression Model (NLIN Procedure); Logistic Growth Model y=A/(1+be-cx) and their rate of change was calculated using its derivate, dy/dx = (Abce-cx)/(1+be-cx)2. The first experiment was carried out from February to May 2018 at (i) four soils which were riverine soil (Tanah Merah, Kelantan), BRIS (Bachok, Kelantan), peat (Simpang Renggam, Johor) and sedentary soil (UPM, Serdang, Selangor) assigned as the main plots with (ii) 1 and 2 row(s) per bed plant arrangements as subplots at (iii) 25 cm and 50 cm planting distances formed as sub-subplots. Results of this study confirms that significant differences in the plant growth, physiological attributes and yield components of sweet corn grown on different soil types, plant arrangements and planting distances. Interaction between peat at 2-row per bed plant arrangement at 25 cm planting distance produced the highest potential plant height at 249.9 cm while peat at 1-row per bed plant arrangement at 50 cm planting distance the best in highest potential in stem diameter at 4.078 cm. Apparently, the interaction between peat with 1-row per bed plant arrangement at 50 cm planting distance; low plant density produced the highest in cob weight (586.9 g), cob length (20.97 cm), cob diameter (5.66 cm), thousand kernel’s weight (459.86 g) and total sugar content (16.25%) which represented quantity per plant. This was reflected by higher growth rates of photosynthesis rate (46.933 μmolCO2m-2s-1), leaf area per plant (1.45 m2) and relative chlorophyll content (58.90%) of each individually plant. However, the interaction between peat with 2-row per bed plant arrangement at 25 cm planting distance; high plant density produced the highest in quantity per hectare (52,426 kg/ha). Based on the results in the first experiment, the second experiment was conducted to increase the quantity component of sweet corn at high plant density using application of plant growth regulators at Research Plot, Biodiversity Unit, Institute of Bioscience, UPM, Serdang, Selangor from September to December 2018 with time of applications i.e. 7 days after planting (vegetative stage) and 40 days after planting (reproductive stage) constituted the main plots and application of different type of plant growth regulators (IBA and GA3) as subplots and different concentrations (0, 50 and 100 mg/L) formed the sub-subplots. In comparison with control, application of GA3 produced the tallest potential plant height at 288.2 cm while application of IBA produced higher potential 3.008 cm in stem diameter both at 100 mg/L during vegetative stage. Interaction between vegetative stage, application of IBA and concentration at 100 mg/L gave the best results on photosynthesis rate (56.32 μmolCO2m-2s-1), leaf area index (18.56) and relative chlorophyll content (63.61%) of plants which in turn gave positive significant impact on its yield components. These interaction factors during both vegetative and reproductive stages improved cob weight (485.31g; 481.00 g), cob length (19.20 cm; 19.40 cm), number of row per cob (15.46; 15.71), number of kernel per row (42.81; 43.10) and thousand kernel’s weight (465.85 g; 462.40 g) of sweet corn. Interaction between IBA and GA3 during vegetative and reproductive stage at 100 mg/L produced the highest cob weight per hectare at 51,734 kg/ha and 51,274 kg/ha. As a conclusion, the results from the study revealed that, sedentary soil produced the least results of plant growth (plant height; stem diameter), physiological attributes (photosynthesis rate; leaf area index; relative chlorophyll content) and yield components compared to BRIS, riverine soil and peat. Even though sedentary soil gave the lowest results, the interaction between 2-row per bed plant arrangement and 25 cm planting distance; higher plant density produced in higher quantity per hectare compared to interaction between 1-row per bed plant arrangement and 50 cm planting distance; low plant density. However, the interaction between 2-row per bed plant arrangement and 25 cm planting distance; higher plant density reduced quantity component per plant produced. In order to improve the quantity component per plant produced reflected of these interaction factors, application of IBA with the highest concentration at 100 mg/L during vegetative stage or reproductive stage significantly improved plant growth, physiological attributes and yield components of sweet corn which finally give positive reflect in quantity per hectare produced.